Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$u\in C^2$ is a solution of the one-dimensional wave equation $u_{tt}=u_{xx}$ with initial values $u(0,x)=f(x)$ and $u_t(0,x)=g(x)$

Now I a little bit confused with the following:

I define a function $v\in C^2(\Omega)$ where $\Omega=\{(a,b)\in\mathbb R^2 | a+b>0\}$ as $v(a,b)=u(a+b,a-b)$

Question 1: I do not see the relation that $u$ is a solution iff $v$ satifies $v_{ab}=0$

My thought was the following: I define $t=a+b, x=a-b$ then $v_{ab}=u_{tx}(t,x)=0$ and from this fact it should somehow be followed that $u_{tt}=u_{xx}$

Question 2: How can it be followed from above that every solution has the form $u(t,x)=F(t-x)+G(t+x)$. What exactly is $F$ and $G$ ?

share|cite|improve this question
up vote 3 down vote accepted

This is based on D'Almbert's solution to the wave equation:

$$u(x,t) = F(x+t) + G(x -t)$$

It follows by substitution into the original equation. You may also consider the transformation $\alpha = x+t$, $\beta=x-t$, so that $x=(\alpha + \beta)/2$, $t=(\alpha-\beta)/2$. Then let

$$ u\left (\frac{\alpha+ \beta}{2}, \frac{\alpha- \beta}{2}\right) = v(\alpha, \beta) $$

$$\frac{\partial u}{\partial x} = \frac{\partial v}{\partial \alpha} \frac{\partial \alpha}{\partial x} +\frac{\partial v}{\partial \beta} \frac{\partial \beta}{\partial x} = \frac{\partial v}{\partial \alpha} + \frac{\partial v}{\partial \beta}$$

$$\frac{\partial u}{\partial t} = \frac{\partial v}{\partial \alpha} \frac{\partial \alpha}{\partial t} +\frac{\partial v}{\partial \beta} \frac{\partial \beta}{\partial t} = \frac{\partial v}{\partial \alpha} - \frac{\partial v}{\partial \beta}$$

By differentiating again in this matter, the wave equation may then be expressed as

$$\frac{\partial^2 v}{\partial \alpha^2} + 2 \frac{\partial^2 v}{\partial \alpha \partial \beta} + \frac{\partial^2 v}{\partial \beta^2} = \frac{\partial^2 v}{\partial \alpha^2} - 2 \frac{\partial^2 v}{\partial \alpha \partial \beta} + \frac{\partial^2 v}{\partial \beta^2} $$

From which follows

$$ v_{\alpha \beta} = 0$$

share|cite|improve this answer
Thank you, but two questions: Using my transformation $u_x=v_a+v_b$ also ? u_tt=? – Voyage Jan 13 '13 at 15:03
If I am getting you right, I answered your questions in my answer. The transformation is really just an application of the chain rule. In terms of operators, $\partial/\partial x = \partial/\partial \alpha + \partial/\partial \beta$, so $(\partial/\partial x)^2 = (\partial/\partial \alpha + \partial/\partial \beta)^2$. Similar for $t$. – Ron Gordon Jan 13 '13 at 15:17
For completeness: Question no. 2 hasn't been answered. An argument of unicity must be performed in order to ensure that every solution has the desired form. – Pragabhava Jan 13 '13 at 15:36
@Pragabhava: Not sure how to go beyond $\partial G(\beta)/\partial \alpha = \partial F(\alpha)/\partial \beta = 0$. Perhaps you have something else to add? – Ron Gordon Jan 13 '13 at 16:02
@rlgordonma I'd say that the fact that $v_{\alpha \beta} = 0$ implies that $v(\alpha,\beta) = F(\beta) + G(\alpha)$ which, in turn, means that $u(x,t) = F(x-t) + G(x+t)$ (this can be ensured because the transformation $(x,t) \to (\alpha,\beta)$ is invertible), and given that the wave equation with initial conditions has a unique solution (provided $f$ and $g$ are in some space, details left to the OP), this has to be it. Finally, using the initial conditions, one can determine $F$ and $G$ in terms of $f$ and $g$, and derive d'Alambert solution. – Pragabhava Jan 13 '13 at 16:14

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.